Dark modes in symmetric bulk Dirac semimetal dimers excited by cylindrical vector beams. (22nd December 2021) - Zhang, Liangang; Ma, Rui; Long, Tianqi; Liu, Guidong; Wang, Ling-ling; Lin, Qi
Abstract: Dark plasmonic modes with sharp spectral resonance peak and exceptionally high quality factor makes it essential for applications in bio-chemical sensing and fluorescence enhancement. Here, we investigate the mid-infrared spectral responses of bulk Dirac semimetal (BDS) dimers under focused azimuthally polarized and radially polarized cylindrical vector beams (CVB). Through numerical simulations, we obtained direct excitation of dark modes and revealed how the beams manipulate the dipole hybridization to produce these modes. By tuning the Fermi energy of BDS, the resonant wavelength of the dark modes can be further adjusted. Our results may find the application of CVB in plasmonic sensing.